Diagnostic and Prognostic Value of the Combination of Two Measures of Verbal Memory in Mild Cognitive Impairment due to Alzheimer's Disease. - Sala, Isabel; Illán-Gala, Ignacio; Alcolea, Daniel; Sánchez-Saudinós, Ma Belén; Salgado, Sergio Andrés; Morenas-Rodriguez, Estrella; Subirana, Andrea; Videla, Laura; Clarimón, Jordi; Carmona-Iragui, María; Ribosa-Nogué, Roser; Blesa, Rafael; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Episodic memory impairment is the core feature of typical Alzheimer's disease. OBJECTIVE: To evaluate the performance of two commonly used verbal memory tests to detect mild cognitive impairment due to Alzheimer's disease (MCI-AD) and to predict progression to Alzheimer's disease dementia (AD-d). METHODS: Prospective study of MCI patients in a tertiary memory disorder unit. Patients underwent an extensive neuropsychological battery including two tests of declarative verbal memory: The Free and Cued Selective Reminding Test (FCSRT) and the word list learning task from the Consortium to Establish a Registry for Alzheimer's disease (CERAD-WL). Cerebrospinal fluid (CSF) was obtained from all patients and MCI-AD was defined by means of the t-Tau/Aβ1-42 ratio. Logistic regression analyses tested whether the combination of FCSRT and CERAD-WL measures significantly improved the prediction of MCI-AD. Progression to AD-d was analyzed in a Cox regression model. RESULTS: A total of 202 MCI patients with a mean follow-up of 34.2±24.2 months were included and 98 (48.5%) met the criteria for MCI-AD. The combination of FCSRT and CERAD-WL measures improved MCI-AD classification accuracy based on CSF biomarkers. Both tests yielded similar global predictive values (59.9-65.3% and 59.4-62.8% for FCSRT and CERAD-WL, respectively). MCI-AD patients with deficits in both FCSRT and CERAD-WL had a faster progression to AD-d than patients with deficits in only one test. CONCLUSIONS: The combination of FCSRT and CERAD-WL improves the classification of MCI-AD and defines different prognostic profiles. These findings have important implications for clinical practice and the design of clinical trials.

Feasibility of Lumbar Puncture in the Study of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease in Subjects with Down Syndrome. - Carmona-Iragui, María; Santos, Telma; Videla, Sebastián; Fernández, Susana; Benejam, Bessy; Videla, Laura; Alcolea, Daniel; Blennow, Kaj; Blesa, Rafael; Lleo, Alberto; Fortea, Juan (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is the main medical problem in older adults with Down syndrome (DS). Studies of cerebrospinal fluid (CSF) AD biomarkers are limited and the feasibility of lumbar puncture (LP) is controversial in this population. OBJECTIVE: To analyze the frequency of complications after a LP in DS. METHODS: We collected data from 80 adults with DS that underwent a LP within the Down Alzheimer Barcelona Neuroimaging Initiative. Demographics, cognitive status, headache history, and presence of complications after the LP were recorded in every subject. In 53 of them (active group), this information was collected following a semi-structured and validated protocol that actively looks for complications. Other variables related to the LP procedure were also recorded. A telephone interview to the caregiver was performed 5-7 days after the procedure to ask about complications. Data from 27 subjects (clinical practice group), from whom the presence of complications was obtained in a medical follow-up visit within the three months after the LP, were also included. RESULTS: There were no adverse events in 90% of our participants. The most frequent complication was headache (6.25%); only one subject reported a typical post-lumbar puncture headache with moderate severity that required analgesic treatment. Dizziness (3.75%) and back pain (1.25%) were also reported. All the participants that reported complications belonged to the active group. CONCLUSION: LP can be safely performed to study CSF biomarkers in DS. The reported complications are qualitatively similar to the general population, but are less frequently reported, even when actively searched for.